2015
DOI: 10.1117/1.jbo.20.7.076010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of light scattering and absorption properties ofin vivorat liver using a single-reflectance fiber probe during preischemia, ischemia–reperfusion, and postmortem

Abstract: Diffuse reflectance spectroscopy (DRS) has been extensively used for characterization of biological tissues as a noninvasive optical technique to evaluate the optical properties of tissue. We investigated a method for evaluating the reduced scattering coefficient μ(s)', the absorption coefficient μ(a), the tissue oxygen saturation StO₂, and the reduction of heme aa3 in cytochrome c oxidase CcO of in vivo liver tissue using a single-reflectance fiber probe with two source-collector geometries. We performed in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…C HbO , C HbR , C HbT , and StO 2 of the normal liver tissue (oxygen breathing and air breathing state) revealed high levels of oxyhemoglobin and tissue oxygen saturation. The large increase in C HbR and decreases in C HbO and StO 2 typically observed in ischemia are consistent with the changes in time courses in StO 2 reported in our previous studies [12,24]. Successive images recorded at 5-min after the onset of reperfusion (t = 25-min) show the spatial changes in C HbO and StO 2 that are indicated by a white arrow on the less perfused portion of the imaged area, which is accompanied with scattered hepatic lobular perfusion.…”
Section: Statistical Considerationssupporting
confidence: 77%
See 3 more Smart Citations
“…C HbO , C HbR , C HbT , and StO 2 of the normal liver tissue (oxygen breathing and air breathing state) revealed high levels of oxyhemoglobin and tissue oxygen saturation. The large increase in C HbR and decreases in C HbO and StO 2 typically observed in ischemia are consistent with the changes in time courses in StO 2 reported in our previous studies [12,24]. Successive images recorded at 5-min after the onset of reperfusion (t = 25-min) show the spatial changes in C HbO and StO 2 that are indicated by a white arrow on the less perfused portion of the imaged area, which is accompanied with scattered hepatic lobular perfusion.…”
Section: Statistical Considerationssupporting
confidence: 77%
“…The results of spatial and temporal changes in C HbO, C HbR , C HbT , StO 2 , and b following ischemia and reperfusion demonstrated that our method is reliable and reproducible for evaluating hepatic hemodynamic parameters and tissue morphology. A notable association is found between the tissue oxygen saturation StO 2 measured using the RGB imaging technique and that measured using a reflectance fiber probe based diffuse reflectance spectroscopy [12,24], which supports the value of the RGB imaging technique in monitoring hepatic tissue perfusion and oxygenation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Diffusely reflected light collected by the central fiber of the fiber probe is delivered to one multichannel spectrometer (USB4000, Ocean Optics Inc.) via another lead of the bifurcated fiber, whereas that collected by the six surrounding fibers of fiber probe is delivered to another multichannel spectrometer (USB4000, Ocean Optics Inc.). Figure 1 depicts a schematic illustration of the optical fiber system developed and utilized by Nishidate et al 34 and Akter et al 35,36 Instrumentation for clinical applications of DRS are presented by Jayanthi et al 37 for detecting oral cancer and Hsu et al 38 for detecting therapeutic response in keloid scar. Jayanthi et al 37 constructed their DRS system (shown in Figure 2) using a tungsten halogen lamp (Model LSI-LL, Ocean Optics, Dunedin, Florida) for tissue illumination and a fiber-optic spectrometer (Ocean Optics; Model: USB 2000FL VIS-NIR) connected to the USB port of a laptop for recording diffuse reflectance spectra from tissues.…”
Section: Drs Instrumentationmentioning
confidence: 99%